A Novel Strategy for Condition Assessment: Predicting Major Adverse Cardiovascular Events Post-Percutaneous Coronary Intervention in Acute Myocardial Infarction Patients via CXCR7 and Its Ligand CXCL12 - Pan, Hong; Fan, Xiaoli; Liu, Yu; Aishan, Gulijiakela; Shao, Jingwen (Journal of Medical Biochemistry, 2025)
Objective: The chemokine receptor CXCR7 and its ligand CXCL12 are critically involved in coronary microenvironment repair. Yet, their clinical relevance in diagnosing acute myocardial infarction (AMI) and forecasting post-percutaneous coronary intervention (PCI) major adverse cardiovascular events (MACE) has not been established. This study aims to explore the diagnostic utility of combined CXCR7 and CXCL12 testing in AMI and its predictive value for post-PCI MACE.  Methods: This study enrolled 162 AMI patients and 54 healthy controls from January to June 2024. All patients received standardized PCI and were followed for 12 months. Serum CXCR7 and CXCL12 concentrations were determined via enzyme-linked immunosorbent assay (ELISA), while NT-proBNP was quantified with an automated biochemical analyzer. Comparative analyses of biomarker levels between groups were conducted, along with receiver operating characteristic (ROC) curve analysis for combined diagnostic performance. Dynamic changes in CXCR7/CXCL12 were also assessed in relation to postoperative MACE.Results: Pre-treatment concentrations of CXCR7 and CXCL12 were markedly higher in the AMI group relative to controls. The combined detection achieved an AUC value of 0.812 for diagnosing AMI, superior to individual indicators (P